2017
DOI: 10.1111/joac.12224
|View full text |Cite
|
Sign up to set email alerts
|

Migration and agrarian transformation in Indigenous Mexico

Abstract: Migration is of particular concern to Indigenous peoples and communities. It physically separates those who migrate from the land upon which collective processes of labour and ritual practice are often based, it affects congruence between individual and collective rationality (as migrants make the choice to maintain or relinquish community membership), and it robs communities of the adult residents who can be essential for projects of collective action. Using the concept of comunalidad, created by Indigenous i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 61 publications
1
25
0
Order By: Relevance
“…Our findings are based on certain key conditions such as economic development and outmigration driven by external forces, labor and capital intensive timber production mode, and small per capita forestland holdings; therefore, our findings are very likely to be valid for communities with these conditions. Studies have shown that the limited dependence on forest income reduces farmers' incentives to make forest investments [3], and that large-scale outmigration hinders the collective actions of managing resources in rural communities [20,56]. These findings indicate that the problem manifested by our case also exists in other regions of China and the world.…”
Section: Discussionmentioning
confidence: 68%
“…Our findings are based on certain key conditions such as economic development and outmigration driven by external forces, labor and capital intensive timber production mode, and small per capita forestland holdings; therefore, our findings are very likely to be valid for communities with these conditions. Studies have shown that the limited dependence on forest income reduces farmers' incentives to make forest investments [3], and that large-scale outmigration hinders the collective actions of managing resources in rural communities [20,56]. These findings indicate that the problem manifested by our case also exists in other regions of China and the world.…”
Section: Discussionmentioning
confidence: 68%
“…This study offers some important caveats in response, showing that many firstgeneration migrants resist (equitably) sharing collective work obligations with village residents. Tension between residents, who disproportionately meet the burden of village governance, and migrants who want to limit their contributions, provides further evidence of incongruence between individual and collective rationalities in Oaxacan commons regimes (Stephen 2007;Gutierrez Najera 2009;Robson et al 2018). While migration cannot be considered the only disrupting force at play, the research presented here suggests that the migratory experience remains significant.…”
Section: Discussionmentioning
confidence: 72%
“…Research is also needed to identify the evolving (and likely divergent) views of those living in their communities of origin, with regards to traditional governance, terms of membership, and shifting power relations within the community sphere. This would help to properly contextualize the role that migration and the migratory experience might be playing in disrupting structures of communal service and identity (Robson et al 2018), particularly in conjunction with broader changes (in village culture, economy, politics, and environment) affecting remote and rural communities (Van de Ploeg 2008;Berdegué, Rosada, and Bebbington 2014;Davidson-Hunt et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These new dynamics include increased schooling, migration and remittance economies, non-agricultural waged activities, government funded conditional cash transfers [200,201], often coupled with dwindling agricultural subsidies [199], and the presence of conservation funding [202]. All in all, the decline of land-based livelihoods, increased schooling and migration are associated with demographic and cultural change [203] and TEK loss [135,204,205], all of which challenges and reshapes communal governance [206].…”
Section: Factors Beyond Government Actions Also Affect the Use Of Tekmentioning
confidence: 99%